2000
DOI: 10.1128/aem.66.2.571-577.2000
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Role of the Branched-Chain Aminotransferase (BcaT) Isolated from Lactococcus lactis subsp. cremoris NCDO 763

Abstract: In Lactococcus lactis, which is widely used as a starter in the cheese industry, the first step of aromatic and branched-chain amino acid degradation is a transamination which is catalyzed by two major aminotransferases. We have previously purified and characterized biochemically and genetically the aromatic aminotransferase, AraT. In the present study, we purified and studied the second enzyme, the branched-chain aminotransferase, BcaT. We cloned and sequenced the corresponding gene and used a mutant, along w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
138
1
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(155 citation statements)
references
References 47 publications
15
138
1
1
Order By: Relevance
“…Evidence was found that the strength of repression by L. lactis CodY correlated with the intracellular pool of branchedchain amino acids (BCAAs) (18, 39). These findings are supported by observations that the growth in milk of an L. lactis strain lacking the aminotransferases AraT and BcaT, which are involved in the catabolism of BCAAs (42,55), is severely affected when isoleucine (Ile) or a dipeptide containing this amino acid is added. Since the growth rate of an L. lactis codY mutant was not altered by addition of Ile, inhibition by this amino acid is probably due to CodY-mediated repression of the proteolytic system, which leads to retarded growth (5, 36).…”
supporting
confidence: 71%
“…Evidence was found that the strength of repression by L. lactis CodY correlated with the intracellular pool of branchedchain amino acids (BCAAs) (18, 39). These findings are supported by observations that the growth in milk of an L. lactis strain lacking the aminotransferases AraT and BcaT, which are involved in the catabolism of BCAAs (42,55), is severely affected when isoleucine (Ile) or a dipeptide containing this amino acid is added. Since the growth rate of an L. lactis codY mutant was not altered by addition of Ile, inhibition by this amino acid is probably due to CodY-mediated repression of the proteolytic system, which leads to retarded growth (5, 36).…”
supporting
confidence: 71%
“…However, growth studies in MS15 and milk suggest no other L. lactis enzyme can transaminate oxaloacetate in vivo efficiently enough to support growth under Asp-limiting conditions. This is consistent with the substrate specificity of the lactococcal aromatic Yvon et al, 1997) and branchedchain (Atiles et al, 2000 ;Yvon et al, 2000) ATases, which lack detectable activity with Asp. Asp also appears to be the only amino acid substrate for AspC.…”
Section: Discussionsupporting
confidence: 71%
“…The oxidative branch of the trichloroacetic acid cycle can provide the cell with ␣-ketoglutarate, which in turn is used in the formation of glutamate by some lactic acid bacterium (58,62). In addition, ␣-ketoglutarate acts as a cosubstrate for the aminotransferase BcaT, which catalyzes the first step of BCAA catabolism (55). Thus, ␣-ketoglutarate provides a connection between BCAA and glutamate metabolism, which could explain why CodY orchestrates transcription of genes involved in the trichloroacetic acid cycle and glutamate biosynthesis (gltDB and lysA) in addition to those concerned with BCAA metabolism (ilv and bcaT).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, although L. lactis MG1363 like many other lactococcal dairy strains is auxotrophic for these amino acids, several genes of the BCAA biosynthetic operon are present on the chromosome and are actively transcribed (1,53). The gene encoding the aminotransferase BcaT, catalyzing either the first step of aromatic or branched-chain amino acid catabolism or the last step of their biosynthesis (54,55), was also significantly derepressed.…”
Section: Role Of Cody In Global Genementioning
confidence: 94%